APPLICATION OF WHATSAPP VOICE NOTE BASED COOPERATIVE LEARNING ON STUDENT COMMUNICATION SKILLS - Pudjastawa, Astrid Wangsagirindra; Cantika, Varary Mechwafanitiara (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research is motivated by the low communication skills of students in Javanese language subjects, especially in class XII students of SMKN 3 Malang. This research was conducted to determine the effect of the Whatsapp Voice Note-based cooperative learning method on online learning on students' communication skills in Javanese. This study uses a pre-experimental method. The subjects consisted of 35 students. Communication skills were measured by written tests (pretest and posttest) and observation sheets. Communication skills tests and observation sheets were prepared and developed based on 21st-century communication indicators. Analysis of written test data (pretest and posttest) in this study were analyzed using statistical tests using the Statistics Package for Social Science (SPSS) software and performed manually using Microsoft Excel 2010 The observation sheet data were analyzed using the percentage calculation results. The data obtained from the study revealed that the application of the Whatsapp Voice Note-based cooperative learning method affected communication skills. This finding might be considered by Javanese language teachers to improve their communication skills. Keywords: Student Communication Skill, Whatsapp Voice Note, Cooperative Learning